2016
DOI: 10.1101/gad.283499.116
|View full text |Cite
|
Sign up to set email alerts
|

Genetic ablation of Smoothened in pancreatic fibroblasts increases acinar–ductal metaplasia

Abstract: The contribution of the microenvironment to pancreatic acinar-to-ductal metaplasia (ADM), a preneoplastic transition in oncogenic Kras-driven pancreatic cancer progression, is currently unclear. Here we show that disruption of paracrine Hedgehog signaling via genetic ablation of Smoothened (Smo) in stromal fibroblasts in a Kras G12D mouse model increased ADM. Smo-deleted fibroblasts had higher expression of transforming growth factor-α (Tgfa) mRNA and secreted higher levels of TGFα, leading to activation of EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 71 publications
8
53
0
Order By: Relevance
“…These results are in agreement with previous studies demonstrating the association of TMEM16A expression with the EGFR signaling pathway in breast cancer and HNSCC (11,12,22). Given that the EGFR signaling pathway in pancreatic cancer relies on the EGFR ligands (13,14) and promotes pancreatic ductal adenocarcinoma (PDAC) development by regulating acinar-ductal metaplasia, cancer cell migration, and the occurrence of metastasis (15,17,18,23), our finding suggests that TMEM16A could play an essential role in ligand-induced EGFR signaling pathway in pancreatic cancer.…”
Section: Tmem16a Is Overexpressed In Pancreatic Ductal Adenocarcinomasupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in agreement with previous studies demonstrating the association of TMEM16A expression with the EGFR signaling pathway in breast cancer and HNSCC (11,12,22). Given that the EGFR signaling pathway in pancreatic cancer relies on the EGFR ligands (13,14) and promotes pancreatic ductal adenocarcinoma (PDAC) development by regulating acinar-ductal metaplasia, cancer cell migration, and the occurrence of metastasis (15,17,18,23), our finding suggests that TMEM16A could play an essential role in ligand-induced EGFR signaling pathway in pancreatic cancer.…”
Section: Tmem16a Is Overexpressed In Pancreatic Ductal Adenocarcinomasupporting
confidence: 92%
“…In pancreatic cancer, the EGFR signaling pathway is involved in both cancer initiation and the development of metastasis (13,14). Unlike breast cancer and HNSCC that are associated with mutations rendering EGFR constitutively active, pancreatic cancer involves activation of the EGFR signaling pathway by extracellular ligands such as EGF, TGF-α, or Epiregulin (15)(16)(17)(18). It is therefore important to determine whether TMEM16A regulates EGFR signaling in pancreatic cancer cells in a manner that depends on ligand activation of EGFR.…”
mentioning
confidence: 99%
“…Activated fibroblasts interplay with epithelial cells in the development of metaplasia through aberrant sonic hedgehog (SHH) signalling 135138 . In the context of Barrett oesophagus, it has been proposed that epithelial cells induce SHH expression, which in turn promotes stromal expression of SHH target genes such as patched 1 ( PTCH1 ) and bone morphogenetic protein 4 ( BMP4 ), and may result in the expression of epithelial SOX9 and cytokeratins 137 .…”
Section: Epigenetic and Genomic Considerationsmentioning
confidence: 99%
“…In the context of Barrett oesophagus, it has been proposed that epithelial cells induce SHH expression, which in turn promotes stromal expression of SHH target genes such as patched 1 ( PTCH1 ) and bone morphogenetic protein 4 ( BMP4 ), and may result in the expression of epithelial SOX9 and cytokeratins 137 . Similarly, it has been shown that in the pancreas, genetic ablation of smoothened ( Smo ), which mediates SHH signalling, in fibroblasts results in the activation of AKT and the transcription factor GLI2 and increased ADM 135,139 . Another factor in the stroma is the transcription factor ETS2.…”
Section: Epigenetic and Genomic Considerationsmentioning
confidence: 99%
“…In the current study by Liu et al (2016), the investigators sought to elucidate how Hedgehog signaling from pancreatic stromal fibroblasts impacts pancreatic acinar-ductal metaplasia (ADM), which is a consequence of cellular plasticity in response to injury (e.g., cerulein-induced acute pancreatitis in mice) and is governed by a set of transcriptional factors, such as Sox9, Prrx1, Mist1, and Ptf1a (Reichert et al 2013). ADM has been established in mice to be a precursor of PanIN and PDACs.…”
mentioning
confidence: 71%